GEMINI output used to develop volumetric reconstruction technique for EISCAT 3D - Reistad, Jone Peter; Zettergren, Matthew (Zenodo, 2024)
This dataset is used as a "ground truth" for investigating the performance of a volumetric reconstruction technique of electric current densities, intended to be applied to the EISCAT 3D radar system. The technique is outlined in a mnuscript in preparation, to be referred to here once submitted. The volumetric reconstruction code can be found here: https://github.com/jpreistad/e3dsecs This dataset contain three files: 1) Dataset file 'gemini_dataset.nc'. This is a dump from the end of a GEMINI model run driven with a pair of up/down FAC above the region around the EISCAT 3D facility. Detailes of the GEMINI model can be found here: https://doi.org/10.5281/zenodo.3528915 . This is a NETCDF file, intended to be opened with xarray in python: import xaray dataset = xarray.open_dataset('gemini_dataset.nc') 2) Grid file 'gemini_grid.h5'. This file is needed to get information about the grid that the values from GEMINI are represented in. The E3DSECS library (https://github.com/jpreistad/e3dsecs) has the necessary code to open this file and put it into the dictionary structure used in that package. 3) The GEMINI simulation config file 'config.nml' used to produce the simulation. This could be used to reproduce the full simulation of the GEMINI model, which is freely available at https://github.com/gemini3d